Hotspots of H1N1 influenza in India: analysis of reported cases and deaths (2010–2017). (April 2020) - Chatterjee, Pranab; Seth, Bhavna; Biswas, Tamoghna
Influenza A (H1N1) caused significant mortality and morbidity globally. We identified the hotspots for H1N1 influenza in India using cases and deaths reported in the Integrated Disease Surveillance Program between 2010 and 2017. A total of 114, 667 cases and 8543 deaths were reported from across India, at an overall case fatality rate of 7.5%. While Maharashtra accounted for 21% of cases and 31% of deaths, Delhi and Gujarat were ranked the highest based on the population-adjusted ranks for morbidity and mortality, respectively. The current analysis identified states and union territories in western India (Delhi, Punjab, Rajasthan, Gujarat and Maharashtra) to be especially vulnerable.